The Role of Event Planner in Event Management: Perspectives of Trail of The King's Event Participants in Lake Toba - Fitriyah, Hesty Nur (SABA: Journal of Tourism Research, 2025)
This study examines the strategic role of event planners in the planning and implementation of the “Trail of The King's” event, an international trail running competition held in Lake Toba, North Sumatra, Indonesia. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and documentation involving six informants, including event organisers and participants. The findings reveal that event planners contribute significantly across all stages of event management—research, design, planning, coordination, and evaluation—by ensuring effective communication, technical preparedness, and logistical efficiency. Participant feedback highlighted high satisfaction levels, particularly in relation to the coordination, information systems, and experiential design of the event. The study concludes by emphasizing the importance of professional competencies in event planning and provides practical implications for enhancing the quality of MICE (Meetings, Incentives, Conventions, and Exhibitions) event management in Indonesia.